1997
DOI: 10.1111/j.1439-0396.1997.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beef type, body weight and dietary protein content on voluntary feed intake, digestibility, blood and urine metabolites and nitrogen retention

Abstract: Summary Six normal‐conformation and six double‐muscled Belgian White‐blue bulls were involved in a 2 × 2 × 2 factorial experiment to investigate the effect of genotype (normal versus double‐muscled), body weight (400 versus 600 kg) and dietary crude protein (135 versus 165 g per kg dry matter) on voluntary feed intake, digestion and its consequences on the nutritive value, metabolites in blood and urine and nitrogen retention. The diet consisted of concentrate and maize silage (50:50, dry matter basis) and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
7
21
0
Order By: Relevance
“…Total tract and ruminal digestibility of OM, NDF, and starch were not negatively influenced by OEB deficit (Table 4). Total tract and ruminal digestibility measured in this experiment were consistent with those generally measured on double-muscled Belgian Blue bulls (Fiems et al, 1997;Valkeners et al, 2006). According to these results, the fiber and starch degradation activities of the rumen microbes were not affected by a lack of ruminally available N, meaning that the energy availability for animal maintenance and growth were the same for the 3 diets.…”
Section: Discussionsupporting
confidence: 88%
“…Total tract and ruminal digestibility of OM, NDF, and starch were not negatively influenced by OEB deficit (Table 4). Total tract and ruminal digestibility measured in this experiment were consistent with those generally measured on double-muscled Belgian Blue bulls (Fiems et al, 1997;Valkeners et al, 2006). According to these results, the fiber and starch degradation activities of the rumen microbes were not affected by a lack of ruminally available N, meaning that the energy availability for animal maintenance and growth were the same for the 3 diets.…”
Section: Discussionsupporting
confidence: 88%
“…The chemical composition and the nutritive value corresponds well with data of De Boever et al (1983) and Lisiń ka and Leszczyń ski (1989). Because of their constant high-energy value, they are interesting feeds for double-muscled animals with a reduced intake capacity (Fiems et al, 1997). Boucqué et al (1982) did not find an increased daily gain in dual-purpose Belgian Blue bulls when the finishing diet contained 40% culled potatoes as a substitute for maize silage.…”
Section: Discussionmentioning
confidence: 99%
“…Potatoes have a high-energy value, mainly as a consequence of a high and constant digestibility of the organic matter (De Boever et al, 1983). Double-muscled animals are characterized by a lower feed intake capacity than non-double-muscled animals (Fiems et al, 1997) and potatoes resulted in an increased intake in Belgian Blue double-muscled (BBDM) finishing bulls (unpublished data). Intramuscular fat content in double-muscled animals is rather low (Fiems et al, 2003), even lower than 1% in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous work with growing BBDM animals showed that performances were low, even when an energy supplement was fed (Fiems et al, 2002b). This is mainly a consequence of the reduced feed intake capacity of double-muscled animals (Fiems et al, 1997). The high moisture content of grass may contribute to the bulk of the diet because of the intracellular water (Forbes, 1995).…”
Section: Introductionmentioning
confidence: 99%